The Effect of Product Quality, Website Quality, and Risk Perception on Purchasing Decisions on the Berrybenka Website - Nazira, Nazira; Sari, Aida; Ambarwati, Dwi Asri Siti (FKIP Universitas Lampung, 2023)
The development of technology today makes many business actors start to appear. The number of business actors causes intense competition, requiring business actors to carry out various strategies to survive in market competition. Furthermore, the large number of internet users has changed the habits and behavior of the Indonesian people, namely changing conventional transactions to online buying and selling transactions. Indonesia has many E-commerce fashion sites that have been popular, and also has outlets in several places, one of which is Berrybenka. The purpose of this study is to determine the effect of product quality variables, website quality, and risk perception on purchasing decisions on the Berrybenka website in Bandar Lampung. The data used in this study are primary data obtained from the results of respondents' answers collected with the help of a questionnaire. The number of samples in this study were 115 respondents. The sample collection method uses purposive sampling, which is a technique used to determine the sample with criteria according to the researcher's determination. The analysis methods used in this study are validity test, reliability test, partial test (t-test), and coefficient of determination (R2). Then the analysis stage uses multiple linear regression analysis with the help of the SPSS 26 application. The results of this study indicate that product quality, website quality, and risk perception have a significant effect on purchasing decisions.Keywords: Product Quality, Website Quality, Purchase Decision, BerrybenkaDOI: http://dx.doi.org/10.23960/E3J/v6i2.207-215